Comparative analysis of viruses in four bee species collected from agricultural, urban, and natural landscapes - Olgun, Tugce; Everhart, Sydney E.; Anderson, Troy; Wu-Smart, Judy (PLOS ONE, 2020)
Managed honey bees (Apis mellifera L.) and wild bees provide critical ecological services that shape and sustain natural, agricultural, and urban landscapes. In recent years, declines in bee populations have highlighted the importance of the pollination services they provide and the need for more research into the reasons for global bee losses. Several stressors cause declining populations of managed and wild bee species such as habitat degradation, pesticide exposure, and pathogens. Viruses, which have been implicated as a key stressor, are able to infect a wide range of species and can be transmitted both intra- and inter-specifically from infected bee species to uninfected bee species via vertical (from parent to offspring) and/or horizontal (between individuals via direct or indirect contact) transmission. To explore how viruses spread both intra- and inter-specifically within a community, we examined the impact of management, landscape type, and bee species on the transmission of four common viruses in Nebraska: Deformed wing virus (DWV), Israeli acute paralysis virus (IAPV), Black queen cell virus (BQCV), and Sacbrood virus (SBV). Results indicated the prevalence of viruses is significantly affected (P < 0.005) by bee species, virus type, and season, but not by landscape or year (P = 0.290 and 0.065 respectively). The higher prevalence of DWV detected across bee species (10.4% on Apis mellifera, 5.3% on Bombus impatiens, 6.1% on Bombus griseocollis, and 22.44% on Halictus ligatus) and seasons (10.8% in early-mid summer and 11.4% in late summer) may indicate a higher risk of interspecific transmission of DWV. However, IAPV was predominately detected in Halictus ligatus (20.7%) and in late season collections (28.1%), which may suggest species-specific susceptibility and seasonal trends in infection rates associated with different virus types. However, there were limited detections of SBV and BQCV in bees collected during both sampling periods, indicating SBV and BQCV may be less prevalent among bee communities in this area.